Filtration–UV irradiation as an option for mitigating the risk of microbiologically influenced corrosion of subsea construction alloys in seawater - Machuca, Laura; Jeffrey, R.; Bailey, Stuart; Gubner, Rolf; Watkin, Elizabeth; Ginige, M.; Kaksonen, A.; Heidersbach, K. (Pergamon, 2014)
The effect of filtration-UV irradiation of seawater on the biofilm activity on several offshore structural alloys was evaluated in a continuous flow system over 90 days. Biofilms ennobled the electrode potential by +400–500 mV within a few days of exposure to raw untreated seawater. Filtration-UV irradiation of the seawater delayed the ennoblement of the steels for up to 40 days and lowered localized corrosion rates in susceptible alloys. Ennobling biofilms were composed of microbial cells, diatoms and extracellular polymeric substances and the bacterial community in biofilms was affected by both the alloy composition and seawater treatment.